Agro-Tourism and Community Development in Papua: Local Perspectives on Economic Opportunities - Dewijanti, Indra Irjani; Samual, Sitti Hadija; Hermawan, Anggita Ekaningtyas; Elmekawy, Ahmed Taha (Advances in Tourism Studies, 2025)
This study explores the intersection of agriculture and tourism in Papua, Indonesia, focusing on the potential of agro-tourism as a driver of sustainable economic development. While much of Indonesia’s agro-tourism research has concentrated on Bali and Java, little is known about how Papuan communities perceive the integration of farming, food heritage, and tourism. Drawing on twelve in-depth interviews with farmers, local entrepreneurs, and community leaders, this study adopts a qualitative, narrative-based approach to examine opportunities and constraints in developing agro-tourism. The findings reveal that tourism provides new economic pathways for farmers through the commercialization of coffee, cacao, and sago-based products, as well as cultural food experiences. At the same time, challenges such as limited infrastructure, market access, and policy support constrain the sector’s growth. Importantly, participants highlighted the cultural significance of agriculture in Papuan identity, suggesting that agro-tourism offers not only economic benefits but also a means of preserving heritage and strengthening community pride. This study contributes to the literature by extending agro-tourism debates into Papua’s under-researched context and provides practical insights for policymakers and NGOs seeking to foster inclusive and culturally grounded tourism development in eastern Indonesia.